Kontroversi Hukum Vaksin, Tinjauan Majelis Tarjih Muhammmadiyah - Tjatur Prijambodo (Universitas Muhammadiyah Surabaya, 2023)
AbstractIn the current era of the Covid-19 pandemic, the Covid Vaccine (Vaccine) has become a hot topic of discussion along with the development of technological advances that have succeeded in creating various kinds of modern medicine. This technological advancement is expected to be able to answer the threat of the emergence of new strains of the Corona Virus which continues to grow. The use of vaccines is certainly the hope of scientists in order to overcome the presence of viruses that take many lives. The administration of the Covid vaccine has become controversial among Muslims, some agree with giving vaccines because vaccines are believed to prevent the occurrence of dangerous diseases caused by the Corona Virus, some do not agree because the human body naturally has immunity that is acquired from birth so there is no need for additional vaccines. From the outside, especially vaccines made from viruses that actually harm the body.Â Keywords: Vaccine, Controvertion, Legal